Folian-cv1 Is a Member of a Highly Acidic Phosphoprotein Class Derived From the Foliated Layer of the Eastern Oyster (Crassostrea virginica) Shell and Identified in Hemocytes and Mantle - Johnstone, Mary Beth; Wheeler, A. P.; Falwell, Elizabeth P.; Staton, Meg E.; Saski, Christopher A.; Mount, Andrew S. (Frontiers in Marine Science, 2019)
The proteins derived from the foliated shell layer of the oyster, Crassostrea virginica, are unusually acidic and highly phosphorylated. Here we report the identification of a gene encoding a member of this class of phosphoproteins that we collectively refer to as folian. Using an in silico approach, a virtual probe was constructed from an N-terminal sequence (DEADAGD) determined for a 48 kDa folian phosphoprotein and used to screen an oyster EST databank. A sequence that matched the N-terminus of the 48 kDa protein was found and used to identify the full-length gene from a C. virginica BAC library. The molecular weight of the deduced gene product is 32 kDa and was named folian-cv1. Genomic Southern analysis revealed two variants of the gene. The mature protein is composed of 43.3% Asp, 32.6% Ser, and 9.1% Glu with 37.5% of the amino acids of the protein potentially phosphorylated. The primary sequence of folian-cv1 is organized in blocks, with a short relatively hydrophobic block at the N-terminus and with the remainder containing low complexity regions largely dominated by aspartic acid and serine. Overall, the protein is predicted to be highly disordered. PCR and sequence analyses identified folian-cv1 expression in the mantle and hemocytes. Immuno-histochemical staining of mantle tissue reveals that cells of the shell-facing epithelium and in the periostracal groove secrete a continuous layer of folian-positive material and that folian-positive hemocytes move through the mantle epithelium. The function in shell formation of folian proteins including folian-cv1 is not known. However, based on the complexity of this class of proteins and the two methods of their delivery to the region of shell formation, it is possible they are involved in diverse ways in this process.